Key Plant, Key Pests: Azalea (Rhododendron spp.) - Juanita Popenoe; Caroline Roper Warwick; Jacqueline Bourdon; David J. Norman (EDIS)
This series of Key Plant, Key Pests publications are designed for Florida gardeners, horticulturalists, and landscape professionals to help identify common pests associated with common Florida flora. This publication, the sixth in the Key Plant, Key Pests series, helps identify the most common pests found on the Azalea.